Effects of acute high-altitude exposure on heart rate variability: a systematic review and meta-analysis - Li, Hao; Chen, Xiangwei; Huang, Cong; Du, Weiping (Frontiers in Physiology, 2026)
ObjectiveThis study aimed to systematically review and meta-analyze the effects of acute high-altitude exposure on heart rate variability (HRV), in order to elucidate the adaptive changes of the autonomic nervous system under high-altitude environments.MethodsFollowing the PRISMA 2020 guidelines, PubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang databases were searched from inception to June 2025. Eligible studies included healthy adults who acutely ascended to high altitude (≥2,500 m, exposure duration ≤7 days) and reported HRV-related indices, including Standard Deviation of Normal-to-Normal intervals (SDNN), Root Mean Square of Successive Differences (RMSSD), Percentage of successive NN intervals differing by more than 50 ms (pNN50), High-Frequency power (HF), and Low-Frequency power (LF). Statistical analyses were performed using Stata 17.0 and RevMan 5.4. Effect sizes were expressed as standardized mean differences (SMDs) with 95% confidence intervals (CIs). Subgroup analyses, sensitivity analyses, and publication bias assessments were also conducted.ResultsA total of 15 studies involving 698 participants were included. Meta-analysis revealed that after acute high-altitude exposure, SDNN, RMSSD, pNN50, HF, and LF were all significantly (all p < 0.001) reduced compared with sea-level values, whereas the LF/HF ratio increased significantly (p < 0.001). Altitude subgroup analysis indicated that at ≥3500 m, SDNN decreased more and LF/HF increased more than at <3,500 m (p < 0.05), while no significant between-group differences were found for RMSSD, pNN50, HF, or LF (all p > 0.05). In the fitness subgroups, SDNN, RMSSD, pNN50, and HF did not differ significantly between trained individuals and healthy adults (all p > 0.05), although trained individuals exhibited a smaller reduction in LF and a more pronounced increase in LF/HF (p < 0.05). Sensitivity analyses confirmed the robustness of the results, and no obvious publication bias was detected.ConclusionAcute high-altitude exposure markedly reduces both time- and frequency-domain HRV indices, accompanied by an increase in the LF/HF ratio, indicating an autonomic response characterized by “reduced variability, vagal withdrawal, and relative sympathetic predominance.” This response becomes more pronounced at higher elevations (≥3,500 m). Both trained and healthy adults experience vagal inhibition; however, trained show better preservation of low-frequency oscillations and stronger sympathetic regulatory capacity. Accordingly, strategies such as gradual ascent, maintaining stable breathing rhythms, and incorporating recovery-focused training before and after entering high altitude may help mitigate autonomic disturbances and facilitate early acclimatization.Systematic Review Registrationhttps://inplasy.com/projects/, identifier INPLASY202590004.